A “Know Thyself!”: Kejelasan konsep diri meningkatkan hubungan berkualitas pada dewasa awal yang berpacaran - Kurniawan, Esther Josephine; Sutanto, Sandra Handayani (Konsorsium Psikologi Ilmiah Nusantara, 2025)
Establishing committed romantic relationships is one of the developmental tasks during emerging adulthood. However, low relationship quality can lead to short-lived romantic relationships. Erikson's theory suggests that the development of romantic relationships in emerging adulthood is influenced by the identity formation tasks in adolescence. Therefore, this quantitative study aims to examine the role of self-concept clarity in relationship quality among emerging adults in a romantic relationship. The Self-Concept Clarity Scale and Quality of Relationship Inventory were used to measure self-concept clarity and relationship quality in 215 emerging adults aged 18-29 who were in a relationship (MAge = 23.619; SD = 2.425), selected through convenience sampling. Results showed that self-concept clarity significantly influences (8.1%) relationship quality among emerging adults in romantic relationships in Jakarta. The result highlights the need to adopt a multicultural approach and balance between collectivist and individualistic values to achieve a more stable self-concept and enhanced relationship quality.